Towards more sustainable organic processes : heterocyclizations in non-conventional solvents - Maner, Asif S.; Carbone, Vincenzo; Gabriele, Bartolo; Mancuso, Raffaella (My University, 2017)
This thesis reports the synthesis of important heterocyclic derivatives by iodocyclization, carbonylation and cycloisomerization reactions in Non-Conventionl solvents like deep eutectic solvents (DES) and Ionic Liquids (ILs). In chapter one general aspects of green and sustainable chemistry and introduction to eco-friendly green solvents such as water, DES, ScCO2 and ILs are described. Carbonylation processes, their advantages, types were described along with the application of transition metal catalysis in the carbonylation reactions with mechanistic approaches discussed. In chapter two, we describe a convenient and general method for the synthesis of substituted thiophenes through heterocyclodehydration and iodocyclization of readily available 1-mercapto-3-alkyn-2-ols in DES as the solvents. In chapter three we discuss a convenient carbonylative approach to 2-oxazolidinone derivatives carried out in an ionic liquid as the solvent (EmimEtSO4) is presented. It is based on the sequential concatenation of two catalytic cycles, both catalyzed by the same metal species (auto-tandem catalysis). In chapter four we present iodocyclization reactions to obtain iodinated isobenzofuranones and isochromenones by iodolactonization of 2-alkynyl benzoic acids in ionic liquids. In particular here we have developed divergent syntheses of (E)-3-(iodoalkylidene) isobenzofuran-1(3H)-ones and 4-iodo-1H-isochromen-1-ones by base-free Iodolactonization of 2-alkynylbenzoic acids in ionic liquids. In chapter five we report the cycloisomerization of readily available 2-alkynylbenzoic acids using an ionic liquid as the reaction medium in the presence of CuCl2 as a simple and inexpensive catalyst. Although in principle two different cyclization pathways can be followed, leading to either 5-exo-dig mode or 6-endo-dig mode, we have found that substrates bearing an aryl group on the triple bond or a terminal triple bond can be selectively converted into the isobenzofuranone derivatives, using N-ethyl-N-methylmorpholinium dicyanamide (Mor1,2N(CN)2) as the solvent. On the other hand, and in a complementary manner, substrates substituted with an alkyl or an alkenyl group on the triple bond selectively led to isochromenones when the reaction was carried out EmimEtSO4 and with excellent recyclability of the catalyst/ionic liquid system.
Ph.D. in Physics, Chemistry and Materials Science and Technology Ciclo XXIX
Keywords: Green chemistry; Ionic solutions